(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper examines the role of student evaluation and feedback in enhancing teaching quality in higher education. Beginning with a comprehensive literature review, the historical context, theoretical frameworks, and previous research on student evaluation effectiveness are explored. Methodologies for implementing student evaluation systems, including sampling procedures, data collection methods, and evaluation instruments, are discussed. The paper analyzes the impact of student feedback on teaching quality, including quantitative and qualitative analyses of survey data, identification of common themes and patterns in student feedback, and changes implemented based on student suggestions. Best practices for maximizing the utility of student feedback and recommendations for policy and practice in higher education are presented. Future directions and research implications are also discussed, highlighting emerging trends, areas for further inquiry, and implications for policy and practice. Overall, this paper provides valuable insights into the importance of student evaluation and feedback as catalysts for continuous improvement in teaching quality in higher education.